2015
DOI: 10.1007/s12010-015-1927-1
|View full text |Cite
|
Sign up to set email alerts
|

SSR Markers Associated with Proline in Drought Tolerant Wheat Germplasm

Abstract: Water stress causes major agricultural loss throughout the world as survival of the crops remained under stress and loss in yield. Plants respond to drought stress by means of different adaptive mechanisms such as accumulation of osmoprotectants to counteract the water stress. Amino acid proline is known to occur widely in higher plants and normally accumulates in large quantities as an osmolyte in response to environmental stresses. Biochemical estimation of proline was done in the drought-affected wheat geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Further, the cytoplasm undergoes extravasation under drought stress, resulting in an increase in relative conductivity [14]. Under drought stress, proline reduces the osmotic potential, plays a role in osmotic regulation, and protects cell membrane structure; these changes represent an adaptive response of plants to adverse environments [60,61,62]. Our results, together with those of previous studies, strongly suggest that TaDrSR1 and TaDrSR2 potentially play vital roles in conferring drought tolerance in common wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the cytoplasm undergoes extravasation under drought stress, resulting in an increase in relative conductivity [14]. Under drought stress, proline reduces the osmotic potential, plays a role in osmotic regulation, and protects cell membrane structure; these changes represent an adaptive response of plants to adverse environments [60,61,62]. Our results, together with those of previous studies, strongly suggest that TaDrSR1 and TaDrSR2 potentially play vital roles in conferring drought tolerance in common wheat.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid break down of proline upon relief of stress may provide sufficient reducing agents that support mitochondrial oxidative phosphorylation and generation of ATP for recovery from stress and repairing of stress-induced damages [29]. Iqbal et al [30] have reported that the accumulation of proline in drought-tolerant and drought-sensitive cultivars has revealed the significance of this osmolyte. The role of proline in induced PEG experiment gave evidence that the higher levels of proline are due to the emergent need of stressed plant.…”
Section: Prolinementioning
confidence: 99%
“…In plants, trehalose increased the biomass production in shoots and roots in all wheat cul tivars under waterstressed conditions as an osmoprotectant under adverse environmental conditions. Exogenous applications of trehalose and proline to plants during or after stress exposure and the increase in the internal levels of these compounds generally enhance plant growth and final crop yield under stress conditions [30].…”
Section: Trehalosementioning
confidence: 99%
“…These markers might be used for marker-assisted selection. Iqbal et al 39 showed that the wheat genotype association with the levels of proline during induced drought stress and the relationship between pattern of drought responsive biochemical attributes and DNA markers in the selected wheat genotypes was recognized to select drought tolerant genotypes. In the same concern, Aly et al 40 demonstrated that peroxidase and polyphenol oxidase activity and gene expressions can be used as biochemical and molecular markers to detect the resistance or susceptibility nature of wheat cultivars against salinity in integration with gamma irradiation.…”
Section: Primer Namementioning
confidence: 99%